2014
DOI: 10.1016/j.juro.2014.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Treatment of Cryptorchidism: AUA Guideline

Abstract: Imaging for cryptorchidism is not recommended prior to referral, which should occur by 6 months of age. Orchidopexy (orchiopexy is the preferred term) is the most successful therapy to relocate the testis into the scrotum, while hormonal therapy is not recommended. Successful scrotal repositioning of the testis may reduce but does not prevent the potential long-term issues of infertility and testis cancer. Appropriate counseling and follow-up of the patient is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
371
0
27

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(444 citation statements)
references
References 44 publications
8
371
0
27
Order By: Relevance
“…In our series, the median age of the boys at the time of referral was 45 months, with 73% of boys referred well beyond the recommended age of <12 months for appropriate surgical management. 9,10 The overuse of ultrasound also adds to the burden on the Canadian healthcare system. A large retrospective study was undertaken by Kanaroglou and colleagues with boys with undescended testis in Ontario, Canada.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, the median age of the boys at the time of referral was 45 months, with 73% of boys referred well beyond the recommended age of <12 months for appropriate surgical management. 9,10 The overuse of ultrasound also adds to the burden on the Canadian healthcare system. A large retrospective study was undertaken by Kanaroglou and colleagues with boys with undescended testis in Ontario, Canada.…”
Section: Discussionmentioning
confidence: 99%
“…According to the 1996 American Academy of Pediatrics recommendation 32 and the recently published American Urological Associaton (AUA) guidelines 33 on the topic, orchidopexy should be performed before one year of age based on changes in the number of germ cells in the UDT that start to occur beyond that age. 34 Results from a randomized, controlled trial comparing testicular growth after surgery performed at nine months vs. at three years of age indicated that early orchidopexy was followed by a partial catch-up testicular growth, which was not seen after late operation.…”
Section: Timingmentioning
confidence: 99%
“…During this process there is also apoptosis of germ cells, and it is postulated that these persistent undifferentiated germ cells may lead to malignancy in the long term13. The latest guidance from several professional associations14, 15, 16, 17, including a recent British Association of Paediatric Urologists (BAPU) consensus statement, recommends performing orchidopexy by 12 months of age.…”
Section: Introductionmentioning
confidence: 99%